Efficient Triplet Exciton Fusion in Molecularly Doped Polymer Light‐Emitting Diodes. Issue 13 (1st February 2017) - Di, Dawei; Yang, Le; Richter, Johannes M.; Meraldi, Lorenzo; Altamimi, Rashid M.; Alyamani, Ahmed Y.; Credgington, Dan; Musselman, Kevin P.; MacManus‐Driscoll, Judith L.; Friend, Richard H.
Abstract : Solution‐processed polymer organic light‐emitting diodes (OLEDs) doped with triplet–triplet annihilation (TTA)‐upconversion molecules, including 9, 10‐diphenylanthracene, perylene, rubrene and TIPS‐pentacene, are reported. The fraction of triplet‐generated electroluminescence approaches the theoretical limit. Record‐high efficiencies in solution‐processed OLEDs based on these materials are achieved. Unprecedented solid‐state TTA‐upconversion quantum yield of 23% (TTA‐upconversion reaction efficiency of 70%) at electrical excitation well below one‐sun equivalent is observed.